Implementation of c 5.0 algorithm for predicting agricultural materials sales stock - Siti Mawaddah; Ali Ikhwan (Institute of Computer Science (IOCS), 2023)
Cv. Mitra Karya Sejati was founded in 1998 by Tardi Sutanto as a trading company in the field of agricultural materials, such as multipurpose fertilizers, pesticides and seeds. CV. Mitra Karya Sejati is often in short supply due to the increasing demand for consumer goods and even some items are not sold, so it is difficult to predict the stock of goods in the warehouse so far based on sales data which is used only as data to report monthly sales results which will then not be used again. Companies need a sales forecasting system to help you plan stock items in the future. The application of C 5.0 to data mining can make it easier for companies to estimate stock of goods based on sales of agricultural materials. The Data Mining application is built using the PHP programming language and MySQL database to reduce inventory planning losses. Through the proposed system can help companies estimate the stock of goods to be provided to minimize losses. The results of this study obtained sales test data identified as bestsellers on a total attribute of 193 on Cu Daun and Dolimite products, identified as unsold by 0, on CU Daun and Dolimit products, so that it has an accuracy value of 100%, this result becomes the company's benchmark in determining inventory and stock sales in the next month.